2012
DOI: 10.1084/jem.20112095
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into MR1-mediated recognition of the mucosal associated invariant T cell receptor

Abstract: Crystal structure and mutagenesis analyses suggest a MAIT TCR–MR1 docking mode distinct from the NKT TCR-CD1d docking mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
217
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(239 citation statements)
references
References 64 publications
22
217
0
Order By: Relevance
“…We did not find amino acid motifs within the CDR3b, although it does contact the MR1-a1 chain 31,32 . The absence of conserved motifs is consistent with the known absence of effects on antigen reactivity on single amino acid substitutions in the CDR3b chain of MAIT TCR 30,46 . We instead found that MAIT cells displayed a bias in the length of the CD3b domain, with the vast majority of the clonotypes …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We did not find amino acid motifs within the CDR3b, although it does contact the MR1-a1 chain 31,32 . The absence of conserved motifs is consistent with the known absence of effects on antigen reactivity on single amino acid substitutions in the CDR3b chain of MAIT TCR 30,46 . We instead found that MAIT cells displayed a bias in the length of the CD3b domain, with the vast majority of the clonotypes …”
Section: Discussionsupporting
confidence: 83%
“…A recent study suggested that the TCRb chain might be less important for MAIT cell stimulation than was previously thought 30 . To investigate whether the TCRVb chains of MAIT cells have unique features, we compared the CDR3b length in MAIT and non-MAIT cells at amino acid level.…”
Section: Cdr3b Length Distribution Differs In Mait and Non-mait Cellsmentioning
confidence: 92%
“…Furthermore, microbial-independent cross-species reactivity between mouse and human MAIT cells and their MR1 orthologs (3) has been previously observed. Position 151 on the MR1 α2 helix was implicated in cross-species reactivity (16), and was further shown to enhance human MAIT cell reactivity when mutated to an alanine (18). Taken together, these observations suggest that MAIT cell reactivity to MR1 appears to be a balance between MR1 availability on the cell-surface, which may be modulated by endogenous, small-molecule ligands that can support MR1 expression and stability, and other features that can enhance TCR binding, such as species-specific differences in the α-helices, in particular at position 151, or the presence of stimulatory smallmolecule ligands from exogenous sources.…”
mentioning
confidence: 99%
“…MR1 encodes an antigen-presenting molecule specialized in presenting microbial vitamin B6 metabolites (41,42). The protein is also involved in the development and expansion of a small population of T-cells expressing an invariant T-cell receptor alpha chain called mucosal-associated invariant T-cells (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…MR1 encodes an antigen-presenting molecule specialized in presenting microbial vitamin B6 metabolites (41,42). The protein is also involved in the development and expansion of a small population of T-cells expressing an invariant T-cell receptor alpha chain called mucosal-associated invariant T-cells (42,43). Mucosal-associated invariant T-cells lymphocytes are preferentially located in the gut lamina propria and therefore may be involved in monitoring commensal flora or serve as a distress signal (44,45).…”
Section: Discussionmentioning
confidence: 99%